Repositioning Scientific Reasoning in Education after COVID-19: A Bibliometric Review - Yuni Arfiani; Dwi Yulianti; Masturi Masturi; Sunyoto Eko Nugroho; Chokchai Yuenyong (Universitas Pancasakti Tegal, 2026)
This study aimed to examine how scientific reasoning has been repositioned in educational research in the post-COVID era through a bibliometric review. Bibliographic data were retrieved from the Scopus database, covering journal articles published between 2021 and 2025. A total of 161 articles were analyzed using Biblioshiny and VOSviewer to identify publication trends, country contributions, collaboration patterns, and thematic structures. The results showed a growing scholarly emphasis on scientific reasoning after COVID-19, particularly in relation to student-centered pedagogies, assessment practices, higher-order thinking skills, and technology-enhanced learning environments. Keyword network analysis revealed scientific reasoning as a central research theme interconnected with inquiry-based learning, problem-based learning, critical thinking, and digital learning contexts. Overlay visualization further indicated emerging research directions involving artificial intelligence and hybrid learning environments. Overall, the findings demonstrated a clear repositioning of scientific reasoning as a foundational competency in post-COVID educational research and provided insights to inform future studies and instructional innovations.